Pengembangan Buku Cerita Bergambar Untuk Siswa Kelas 2 SD Tunas Dharma Karawang - grace neolaka; Benedicta Aryningtyas Jiwantono (Elementary Teacher Education Program, Majalengka University, 2023)
This development research was sparked because the material provided needed to be tailored to the needs of students and class II students. Students and students need more explanation about clean and healthy environmental material. The purpose of this study is to produce a picture book with clean and healthy environmental material for grade II students to increase reading interest, reading comprehension, and awareness and concern for a clean and healthy environment during the Covid 19 pandemic. The research method was carried out by modifying the development method of Borg. and Gall. Product validation is done through storybook experts and design experts. the validation results have an average value of 3.88 which means good. The final product is an electronic storybook in PDF format. Based on the results of the validation, the researcher concluded that the illustrated storybook with healthy and clean environmental material was worthy of being a source of reading material and media in learning for grade II students at SD Tunas Dharma.